Hypothyroid phenotype is contributed by mitochondrial complex I inactivation due to translocated neuronal nitric-oxide synthase - Franco, M.C. (2006)
Although transcriptional effects of thyroid hormones have substantial influence on oxidative metabolism, how thyroid sets basal metabolic rate remains obscure. Compartmental localization of nitric-oxide synthases is important for nitric oxide signaling. We therefore examined liver neuronal nitric-oxide synthase-α (nNOS) subcellular distribution as a putative mechanism for thyroid effects on rat metabolic rate. At low 3,3′,5-triiodo-L-thyronine levels, nNOS mRNA increased by 3-fold, protein expression by one-fold, and nNOS was selectively translocated to mitochondria without changes in other isoforms. In contrast, under thyroid hormone administration, mRNA level did not change and nNOS remained predominantly localized in cytosol. In hypothyroidism, nNOS translocation resulted in enhanced mitochondrial nitric-oxide synthase activity with low O2 uptake. In this context, NO utilization increased active O2 species and peroxynitrite yields and tyrosine nitration of complex I proteins that reduced complex activity. Hypothyroidism was also associated to high phospho-p38 mitogen-activated protein kinase and decreased phospho-extracellular signal-regulated kinase 1/2 and cyclin D1 levels. Similarly to thyroid hormones, but without changing thyroid status, nitric-oxide synthase inhibitor Nω-nitro-L-arginine methyl ester increased basal metabolic rate, prevented mitochondrial nitration and complex I derangement, and turned mitogen-activated protein kinase signaling and cyclin D1 expression back to control pattern. We surmise that nNOS spatial confinement in mitochondria is a significant downstream effector of thyroid hormone and hypothyroid phenotype. © 2006 by The American Society for Biochemistry and Molecular Biology, Inc.